Physics laboratory manual on mechanics and energy - Malenab, Ryan G. (Manila, Philippines : Rex Book Store, 2002)
This laboratory manual is designed to accompany the Simplified Physics Work/ Textbook made by its authors. In preparing for this laboratory manual, many alterations and additions have been accepted with the object of fitting the experiment described herein more closely to the treatment of the various subjects in most college physics that are being offered, and also of rendering the book more suitable to be placed in the hands of the students and used by them in the least amount of direction from the teacher.